Characterization of microRNA candidates at the primary site of infectious bronchitis virus infection: A comparative study of in vitro and in vivo avian models. - Kelsey O'Dowd; Safieh Vatandour; Sadhiya S Ahamed; Martine Boulianne; Charles M Dozois; Carl A Gagnon; Neda Barjesteh; Mohamed Faizal Abdul-Careem (PLoS ONE)
Infectious bronchitis virus (IBV) is an important avian pathogen with a positive-sense single-stranded RNA genome. IBV is the causative agent of infectious bronchitis (IB), a primarily respiratory disease affecting chickens, with the ability to disseminate to other organ systems, such as the gastrointestinal, renal, lymphoid, and reproductive systems. Tracheal epithelial cells are the primary target of IBV, and these cells play a vital role in the effective induction of the antiviral response and eventual clearance of IBV. The host immune system is regulated by a number of different molecular players, including micro-ribonucleic acids (microRNAs), which are small, conserved, non-coding RNA molecules that regulate gene expression of complementary messenger RNA (mRNA) sequences, resulting in gene silencing through translational repression or target degradation. The goal of this study was to characterize and compare the microRNA expression profiles in chicken tracheal epithelial cells (cTECs) in vitro and the trachea in vivo upon IBV Delmarva/1639 (DMV/1639) or IBV Massachusetts 41 (Mass41) infections. We hypothesized that IBV infection influences the expression of the host microRNA expression profiles. cTECs and young specific pathogen-free (SPF) chickens were infected with IBV DMV/1639 or IBV Mass41 and the microRNA expression at 3 and 18 hours post-infection (hpi) in the cTECs and at 4 and 11 days post-infection (dpi) in the trachea were determined using small RNA-sequencing (RNA-seq). We found that the profile of differentially expressed (DE) microRNAs is largely dependent on the IBV strain and time point of sample collection. Furthermore, we predicted the interaction between host microRNA and IBV viral RNA using microRNA-RNA interaction prediction platforms. We identified several candidate microRNAs suitable for future functional studies, such as gga-miR-155, gga-miR-1388a, gga-miR-7/7b and gga-miR-21-5p. Characterizing the interaction between IBV and the host cells at the level of microRNA regulation provides further insight into the regulatory mechanisms involved in viral infection and host defense in chickens following IBV infection.